Detection of maternal cell contamination in amniotic fluid cell cultures using fluorescent labelled microsatellites. Issue 1 (January 1995) - Smith, G W; Graham, C A; Nevin, J; Nevin, N C
Abstract : A rapid PCR based assay was used to ascertain the presence of maternal cell contamination (MCC) in amniotic fluid cell cultures and to exclude MCC in cases where cytogenetic analysis was possible only from one primary cell culture. Six 6-carboxyfluorescein (FAM) and three 6-carboxyfluorescein hexachloride (HEX) labelled primer sets were used to amplify two tetra- and seven dinucleotide repeat polymorphisms. The PCR amplifications were multiplexed in (three) three primer set reactions and visualised on an Applied Biosystems 373A sequencer running Genescan 672 software. The microsatellite products obtained from 200 amniotic fluid cell cultures where the karyotype was female were compared against corresponding maternal blood PCR products. A single case of MCC was detected indicating the usefulness of such assays. We suggest that screening for MCC should be considered in instances where the amniotic fluid sample is bloodstained or was obtained with difficulty, or where the karyotype is female and chromosome analysis is not possible from more than one primary cell culture.